Indoor Air Quality: From Sampling to Risk Assessment in the Light of New Legislations - Avino, Pasquale; Settimo, Gaetano (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue aims to make a concrete technical contribution to the solution of the various problems related to indoor air pollution. In 11 papers, international scientists report the last findings in this field from different points of view including topics such as the IAQ legislation, the role of IAQ in schools, hospitals and (micro)environments in general, the performance of an olfactometer system or the impact of an indoor malodor, BTEX measures in a Fire Station, and a chemical characterization of e-cigarette (e-cig) refill liquids (e-liq). It seems appropriate to encourage the development of reference values or specific action values in order to better manage particularly problematic situations in these environments. In the absence of national references to be used for a comparison, it is possible to use those reported in the legislation of other European countries or, by ad hoc working groups or by analogy, to use other standards such as those relating to ambient air.